1986
DOI: 10.1002/ajpa.1330700307
|View full text |Cite
|
Sign up to set email alerts
|

An elemental analysis of archaeological bone from Sicily as a test of predictability of diagenetic change

Abstract: Cortical human bone samples from three tightly dated components of a single Sicilian site were chemically analyzed employing the highly sensitive technique of inductively coupled plasma emission spectroscopy. Although the skeletons appeared to be excellently preserved, significant diagenesis was detected. Moreover, a majority of the elements tested showed no constant or linear variation over time, implying that diagenetic change tends not to be a predictable function of duration of interment. Variation among m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

1988
1988
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 17 publications
1
12
0
1
Order By: Relevance
“…Results and Discussion These results are rather similar to those obtained by Klepinger et al (1986), who found a remarkable und unpredictable intraindividual variatiop_ A high intraindividual variability was also noted by Herrmann and Grupe (1987).…”
Section: Methodssupporting
confidence: 89%
See 1 more Smart Citation
“…Results and Discussion These results are rather similar to those obtained by Klepinger et al (1986), who found a remarkable und unpredictable intraindividual variatiop_ A high intraindividual variability was also noted by Herrmann and Grupe (1987).…”
Section: Methodssupporting
confidence: 89%
“…An explanation could lie in the dishomogeneity of the bone tissue (Klepinger et al 1986) or in metabolic differences in the various body districts, but this would not account for a different behaviour from the same skeletal element (such as ribs and vertebrae of this sample). Diagenetic changes due to various species of microorganisms (Grupe and Piepenbrink 1987) and/or to localized differences in the geochemical environment of the burial, could increase the intraindividual variability.…”
Section: Methodsmentioning
confidence: 92%
“…The significance of diagenesis in trace element studies of bone is reflected by the amount written on it (e.g. Waldron et al, 1979;Waldron, 1981Waldron, , 1983Lambert et al, 1985Lambert et al, , 1989Lambert et al, , 1990Kyle, 1986;Klepinger, Kuhn & Williams, 1986;Grupe, 1988;Pate & Hutton, 1988;Price, 1989;Sillen, 1989;Price et al, 1992;Sandford, 1993;Edward & Benfer, 1993). Lead may be taken up by bone from soil, or leeched from bone, although there is some question about which takes primacy (compare Jaworowski, 1990: 176-181, with Patterson et al, 1987.…”
Section: Diagenesismentioning
confidence: 98%
“…However, long, compact bones may not always be preserved from alteration, as indicated by the highly variable intra-bone elemental content of archaeological skeletons (Keplinger et al, 1986). Here we propose to use the intra-skeletal variability in trace element content in order to control for post-mortem changes.…”
Section: Introductionmentioning
confidence: 97%